SPASIALISASI DAN INDIKASI KONGLOMERASI PERUSAHAAN MEDIA TRANS CORP - Muhammad Wildan Hilmansyah (LPSDI Bina Patria, 2023)
The purpose of this research is to uncover and identify the processes of aggregation and spatialization in Trans Corp. Conglomeration and spatialization are used to strengthen dominance through the impact of spatialization. The research approach employed is a qualitative description of Vincent Mosco's critical paradigm of the Political Economy Theory of Communication. This study employs data gathering strategies such as watching and studying Trans Corp.'s operations and its business units through documentation obtained from various textual sources and literature. According to the research findings, Trans Corp.'s spatialization supports the establishment of uncompetitive commercial competitiveness. Trans Corp employs spatialization through horizontal and vertical integration to optimize, reinforce, simplify, and lower the cost of manufacturing elements for the company's long-term viability. Acquisitions, mergers, and the establishment of new business units, both related to the media and unrelated to their core capabilities. This occurrence is in violation of the terms of Law No. 32 Concerning Broadcasting, which prohibits monopolistic ownership and promotes fair business competition in broadcasting, as well as Law No. 5 Concerning the Prohibition of Monopolistic Practices and Unfair Business Competition, Article 18 Paragraph (1) in which spatialization has an impact on the concept of diversity of ownership. Government policy in this kind of conglomerate must also be firm. The goal is to limit diversity of ownership, which will affect diversity of conten